Shaped for service : ministerial formation and virtue ethics - Goodliff, Paul (Lutterworth Press, 2017)
"In the English-speaking Western world alone, thousands of men and women begin formal training for Christian ministry each year, or informally, seek to equip themselves for pastoral ministry. Over the past fifty years, the ancient world of virtue ethics has been reimagined as a means of forming people of character and morality today, and in this book, it is used as the framework to understand what we are doing as we form Christian ministers now, and how we might strengthen that formation by more consciously linking the practices of ministry with the person, spirituality, and wisdom of the practitioner. Writing out of the context of a lifetime of pastoral ministry and the oversight of ministers in the Baptist Union of Great Britain, Paul Goodliff explores what pastors do and who they are called to be, using a mixture of theological and pastoral inquiry, reflections upon art, and personal story. This book will be of interest to those who are charged with forming the next generation of ministers; but anyone starting out on that journey of formation for ministry will also find this vision of ministry challenging and inspiring."--